1984
DOI: 10.1002/j.1460-2075.1984.tb02164.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression is conferred by a sequence from the 5′ end of the rat albumin gene.

Abstract: We have constructed a transient expression vector containing 400 bp of rat albumin gene immediate 5′‐flanking sequences inserted 5′ to the bacterial enzyme chloramphenicol acetyl transferase (CAT). We have transfected various clones of rat hepatoma cells representing different states of expression of the liver phenotype with this vector (pALB‐cat) and also with two control vectors containing viral promoters (pSVE‐cat and pRSV‐cat), and measured activity of the bacterial enzyme CAT in cellular extracts 48 h lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(90 citation statements)
references
References 39 publications
(24 reference statements)
2
87
1
Order By: Relevance
“…Transcriptional regulation in liver cell types has been mainly studied in hepatoma cell lines (Ott et al, 1984;Shaw et al, 1996) although, recently, primary hepatocytes have been shown to express promoter-reporter gene constructs (Hahn et al, 1991 ;Le Cam et al, 1994;Trottier et al, 1995) in the presence of added extracellular matrix components. Other models have been developed, such as the spheroid or sandwich methods, but they have been poorly described with regard to their potential to maintain drug metabolism capacities (Bader et al, 1994(Bader et al, , 1996Koebe et al, 1994;Niwa et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional regulation in liver cell types has been mainly studied in hepatoma cell lines (Ott et al, 1984;Shaw et al, 1996) although, recently, primary hepatocytes have been shown to express promoter-reporter gene constructs (Hahn et al, 1991 ;Le Cam et al, 1994;Trottier et al, 1995) in the presence of added extracellular matrix components. Other models have been developed, such as the spheroid or sandwich methods, but they have been poorly described with regard to their potential to maintain drug metabolism capacities (Bader et al, 1994(Bader et al, , 1996Koebe et al, 1994;Niwa et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very likely that hypomethylation and hypersensitivity to DNase I interact to define regulatory regions of these genes. In this context, data concerning the albumin and AFP regulatory regions were collected by either transient expression assays (14,25,31,55) (25); (ii) the AFPII and M-1 sites are positioned in a region defined as a tissue-specific enhancer (25; A. Pollard, unpublished results); and (iii) AFPIII and M-3 are located within a region defined as a specific silencer (25). It is thus likely that these specific alterations in chromatin structure would expose cis-acting regulatory region so that trans-acting factors could then be bound (9,60).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid ALB-CAT, which contains the rat albumin promoter region (-390 to + lo), has been already described [5]. Plasmid TK-CAT (constructed by Ph.…”
Section: Transient Expression Vectorsmentioning
confidence: 99%